Variabilite Des Extremes Pluviometriques Sur Le Bassin Versant De La Riviere Bia (Sud-Est, Cote d’Ivoire) - Martin, Kouassi Kan; Lazare, Kouassi Kouakou; Blaise, Yao Koffi; Hermann, Meledje N’diaye; Jean, Biemi; Théophile, Lasm; Rouché, Nathalie (European Scientific Journal, ESJ, 2018)
Climate change is a reality which affects many climatic variables, including precipitation. The objective of this article is to study the extreme rain variability from a historical database (1941 - 2000). For this purpose, eleven (11) rainfall indices were calculated at the Adiaké, Bianouan, Ayamé, and Agnibilekro rainfall stations in Côte d’Ivoire. Due to lack of data on daily rainfall on the Ghanaian section of watershed, nine (9) monthly precipitations indices were estimated from monthly rainfall at the Enshi and Buakuc stations. The trend analysis of the precipitations indices show that a generalized downward was most significant in Adiaké compared to other stations. Furthermore, indices extreme thresholding (P99, P99p, P99,5 and P99,5p) have experienced a stable trend and a stationary evolution. All steps were detected in the non-stationary indices mostly observed after 1980 (late break) and before 1960 (precocious break).